Socrates Seen in Ontario Highschools (And He Has Not Left the Building!) - Graham McDonough; Dwight Boyd (University of Windsor, 2009)
Philosophy is a relatively new subject in Ontario Highschools, and the teacher education programs that serve this subject area are even newer. It is laudable that high school students have this opportunity, especially since the intellectual habits of critical thinking and healthy skepticism that philosophy promotes run counter to the traditional educational experiences that students have in many other subjects. However, very little is known about how teachers imagine their role and the "proper outcomes" of this course. We examine interview data concerning how high school philosophy teachers conceptualize their ideal pedagogical aims. This question goes to the heart of why these courses are so important because curriculum is always filtered through teachers' interpretations of it and the aims of education. Teachers look to Socratic questioning and critical thinking as the paragon of philosophical habits, but their responses reveal that "institutional constraints" and "sources of bias" pose two major impediments to this ideal. We focus on these impediments to underscore the importance of the teacher's role and efforts in philosophy classes, and to encourage those in teacher education to take them seriously in designing courses in the new "teachable subject area" of philosophy in Ontario faculties of education.